The rules do not apply ebook A memoir. - Levy, Ariel (2017)
NEW YORK TIMES BESTSELLER •  “This Year’s Must-Read Memoir” ( W magazine) about the choices a young woman makes in her search for adventure, meaning, and love NAMED ONE OF THE BEST BOOKS OF THE YEAR BY Vogue • Time • Esquire • Entertainment Weekly • The Guardian • Harper’s Bazaar • Library Journal • NPR  All her life, Ariel Levy was told that she was too fervent, too forceful, too much. As a young woman, she decided that becoming a writer would perfectly channel her strength and desire. She would be a professional explorer—“the kind of woman who is free to do whatever she chooses.” Levy moved to Manhattan to pursue her dream, and spent years of adventure, traveling all over the world writing stories about unconventional heroines, following their fearless examples in her own life. But when she experiences unthinkable heartbreak, Levy is forced to surrender her illusion of control. In telling her story, Levy has captured a portrait of our time, of the shifting forces in American culture, of what has changed and what has remained. And of how to begin again. Praise for The Rules Do Not Apply “Unflinching and intimate, wrenching and revelatory, Ariel Levy’s powerful memoir about love, loss, and finding one’s way shimmers with truth and heart on every page.” —Cheryl Strayed “Every deep feeling a human is capable of will be shaken loose by this profound book. Ariel Levy has taken grief and made art out of it.” —David Sedaris “Beautifully crafted . . . This book is haunting; it is smart and engaging. It was so engrossing that I read it in a day.” — The New York Times Book Review “Levy’s wise and poignant memoir is the voice of a new generation of women, full of grit, pathos, truth, and inspiration. Being in her presence is energizing and ennobling. Reading her deep little book is inspiring.” — San Francisco Book Review “Levy has the rare gift of seeing herself with fierce, unforgiving clarity. And she deploys prose to match, raw and agile. She plumbs the commotion deep within and takes the measure of her have-it-all generation.” — The Atlantic “Cheryl Strayed meets a Nora Ephron movie. You’ll laugh, ugly cry, and finish it before the weekend’s over.” — theSkimm